Mould design and manufacturing considerations of honeycomb biocomposites with transverse fibre direction for aerospace application - Manan, Nor Hafizah; Abang Abdul Majid, Dayang Laila; Romli, Fairuz Izzuddin (IOP Publishing, 2016)
Sandwich structures with honeycomb core are known to significantly improve stiffness at lower weight and possess high flexural rigidity. They have found wide applications in aerospace as part of the primary structures, as well as the interior paneling and floors. High performance aluminum and aramid are the typical materials used for the purpose of honeycomb core whereas in other industries, materials such as fibre glass, carbon fibre, Nomex and also Kevlar reinforced with polymer are used. Recently, growing interest in developing composite structures with natural fibre reinforcement has also spurred research in natural fibre honeycomb material. The majority of the researches done, however, have generally emphasized on the usage of random chopped fibre and only a few are reported on development of honeycomb structure using unidirectional fibre as the reinforcement. This is mainly due to its processing difficulties, which often involve several stages to account for the arrangement of fibres and curing. Since the use of unidirectional fibre supports greater strength compared to random chopped fibre, a single-stage process in conjunction with vacuum infusion is suggested with a mould design that supports fibre arrangement in the direction of honeycomb loading.